Specificity of Professional Training of Students-Psychologists - Bazarbayeva Aynura Bakhtiyarovna (Research Parks Publishing LLC, 2022)
The article discusses the features of the use of psychological teaching methods in the educational process. The question of the formation of the student's readiness for the upcoming professional activity, as well as the personal development of the future specialist, today remains one of the topical issues addressed by employees of various educational institutions.